(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study examines the policy of implementing non-cash transactions in local governments in Indonesia. 339 respondents are actors in local government spending. The data is processed with SmartPLS. The results of data analysis show that the implementation of the Non-Cash Transaction variable is carried out modestly and reduces fraud in local government spending. The fraudulent behavior of actors outside the local government system apparently affects the occurrence of fraud in local governments, because this factor is not a research variable and is only found during field observations, this factor still needs to be re-examined.